Design and fabricate the portable and adjustable dining chair for child - Nabilah, Harmain (2008)
In this project, this dining chair for child is designed to make parents easier to handle their child during in daily activities. The objectives for my project are to make the chair is suitable in any areas either at home or outside. Besides that, this project is designed to save of space when use or after use it. We can easier to carry and also storage the dining chair anywhere we want to go such as travelling and so on. This involves the process of designing the dining chair for child by considering the shape, the ergonomic factor and also the safety factors. Several methods and processes involved are conceptual design, material selection, cutting, drilling, welding and finishing. After all the processes had been done, this dining chair may help us to understand the fabrication and designing process that involved in this project